Pengembangan Media Pembelajaran Booklet Berbasis Augmented Reality Untuk Meningkatkan Motivasi Belajar Peserta Didik SMA - Muliyani, Rita; Medriati, Rosane; Putri, Desy Hanisa (Navigation Physics : Journal of Physics Education, 2024)
This study aims to assess the feasibility of developing an Augmented Reality-based booklet, measure its impact on student learning motivation, and gauge student responses to the instructional media. The research employs the Research and Development (RND) method, applying the ADDIE model, which involves the stages of Analysis, Design, Development, Implementation, and Evaluation.The validation results from the product validator indicate an overall average percentage of 88.9%, categorized as highly feasible. The developed booklet successfully enhances students' learning motivation, as evidenced by an N-gain score of 0.48 (moderate category). Based on response surveys, the findings are highly favorable, with media scoring 87%, content 94%, and usefulness 97%.These conclusions are further supported by the increased scores in students' learning motivation, demonstrating that the use of the booklet as an instructional medium effectively enhances student motivation to learn.